Nutritional Status of 1-5 Years Children of the Tea Workers in Sylhet Division (Bangladesh Journal of Child Health, 2010)
A cross-sectional community based study was conducted in four tea gardens ofSylhet division to assess the nutritional status of 1 to 5 years children of tea workers.Nutritional status was determined anthropometrically along with their socioeconomicbackground and the nutritional status was compared with the data obtainedfrom national survey. Prevalence of wasting was 42.3% whereas that of stuntingand underweight was 80.2% and 73% respectively. All these parameters are significantlyhigher than those obtained from national data (BDHS, 07). Though thechildren are breast fed at much higher rate in comparison with Bengali children,their mother’s educational status and body mass index are lower than that of Bengalipopulation. The nutritional status of children of tea workers are worse than that ofnational level.Key words: Tea workers; nutritional status.DOI: 10.3329/bjch.v34i1.5696Bangladesh Journal of Child Health 2010; Vol.34(1): 11-16